Job Exposure Matrix: Occupational Exposure Assessment to Carcinogenic Compounds - Moradpour, Zahra; Mosavi Jarrahi, Seyed Alireza (Asian Pacific Journal of Environment and Cancer, 2023)
The Job Exposure Matrix (JEM) is a cross-tabulation of workplace and job title hazards and is an essential exposure assessment tool for epidemiological studies, cancer risk monitoring, cancer risk prevention, and cancer risk quantification in health research and occupational safety. The matrices are designed based on two population-based and industry-based approaches. In the population-based matrix, all occupations of a population are recorded, and in the industry-specific matrix, the occupations in one or more industries are recorded. Exposure to carcinogens factors is measured based on the type of exposure, taking into account three factors including intensity, period and frequency of exposure. Using job exposure matrix in epidemiological studies is easier than other traditional exposure assessment methods and leads to more saving of resources, and sometimes it is the only possible way to analyze causal relationships in very large databases.